Beg, borrow, or steal : a novel [large type] - Adams, Sarah, 1991- (Thorndike Press large print romance series., 2025)
"Jack Bennett is the opposite of the heroes Emily Walker dreams up in her double life as a romance writer, which is why she was perfectly happy when he left Kentucky with his fiancée. The last thing Emily saw coming was Jack's return, but he's here to stay--as her colleague and neighbor. With their animosity at an all-time high, Emily accidentally sends an email to their school's principal that could reveal her secret literary side hustle. She needs to steal back her manuscript, and Jack- she hates to admit- is just the man to help her. Will their unlikely alliance put an end to their rivalry? Or could it lead to a steamy plot twist they never saw coming?"--